Partisipasi Masyarakat Dalam Pembangunan Desa Wisata Pertanian - Nurlatifah, Habibah Sifa’U; Priyanti, Evi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Karang Mukti Village is a village that has potential in tourism agriculture. This potential can be seen from the natural resources in Karang village Mukti where most of the land is agricultural land. This destination has a good chance if it is developed together. However community participation in Karang Mukti village is still lacking, according to the village head Karang Mukti, that this village is still not fully participated by the community participate even when there are village activities. There is a problem disclosed by the Head of Karang Mukti Village, the focus of the research is to do is to identify how participation in the community Karang Mukti village towards the development of an agricultural tourism village. For research towards community participation using qualitative research, in research This qualitative research aims to understand the social conditions in the environment researched. As well as communicative interaction with the environment researched. The results obtained in the research conducted are the community not fully participate in the decision-making process development of agricultural tourism villages, even though the village government has provided information/directions but there are still people who care less and lack active.